Teaching NeuroImages: Comatose patient with bilateral thalamic infarct due to internal carotid artery occlusion - Dababneh, Haitham (Lippincott Williams & Wilkins, 2013)
An 88-year-old woman with a medical history of diabetes, hypertension, and atrial fibrillation presented to the emergency room after being found unresponsive with a NIH Stroke Scale score of 23 and Glasgow Coma Scale score of 3. She was unresponsive to painful stimuli. Noncontrast CT demonstrated bilateral thalamic infarcts (figure 1A).